Factors that Influence Student Decisions in Purchasing Instant Noodle Products of The Sedaap "Goreng" Brand at Jember State Polytechnic - Frida, Lutmika; Muksin; Ambarkahi, Ratih Puspitorini Yekti (Jurnal Manajemen Agribisnis dan Agroindustri, 2023)
This study reveals influences on consumer behavior, especially students on purchasing decisions, by analyzing the factors that influence students' purchasing decisions for Brand Sedap Instant Fried Noodles products. In this study reveals the influence of cultural factors, social, personal, psychological and marketing strategy either jointly or partially, and includes also the dominant factors that influence the purchasing decision product Brand Sedap Instant Fried Noodles, particularly in the State Polytechnic of Jember . The analytical tool used in this study is multiple regression analysis. Overall the results of this study can be concluded that cultural factors, social, personal, psychological and influential marketing strategies together to consumer decisions to buy product Brand Sedap Instant Fried Noodles. Partially, cultural factors, social, psychological and marketing strategies significantly influence on the partial test. For the most dominant factor influencing the purchase decision product Brand Sedap Instant Fried Noodles is a factor of the marketing strategy.